ANTAGONISM AT THE GLYCINE SITE ON THE NMDA RECEPTOR REDUCES SPINAL NOCICEPTION IN THE RAT - (:unkn) unknown (ELSEVIER SCI IRELAND LTD, 1991)
The effects of 7-chlorokynurenate (7CK), an antagonist at the allosteric glycine site associated with the N-methyl-D-aspartate receptor, applied intrathecally, were tested on nociceptive neurons in the dorsal horn of the anaesthetized rat. 7CK reduced the frequency dependent potentiation (wind-up) of the cells to repeated C-fibre stimulation and the related post-discharges at doses which had minimal effects on the C and A-fibre inputs onto the cells although these were reduced by higher doses of the antagonist. Only the effects on post-discharges and wind-up were reversed by application of glycine. Furthermore the neuronal responses to formalin were also reduced by 7CK at doses which did not influence input. The results show that activation of the glycine site is a requirement for spinal NMDA receptor activation and further emphasize the involvement of this receptor in maintained nociceptive processes.
Keywords: NMDA RECEPTOR; DORSAL HORN; GLYCINE; NOCICEPTION; WIND-UP; 7-CHLOROKYNURENIC ACID; NEURONS; MOUSE; CORD; ACID